Membangkitkan kesadaran beragama resident/clien dalam proses rehabilitasi di Yayasan Rumah Ummi di Kecamatan Medan Sunggal Kota Medan - Nelvitia Purba; Sri Sulistyawaty; Ahmad Darwis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The abuse and distribution of narcotics in the city of Medan have been very worrying lately, almost all groups are the target, especially teenagers and young people, Narcotics include extraordinary crimes (extraordinary crime) that are very destructive than physical and mental than the next generation of the nation. Therefore a rehabilitation center that meets standards is needed. Rehabilitation is an effort to restore and restore the condition of victims and drug abuse to return to physical, psychological, social and spiritual health. So far the Ummi House rehabilitation center has not been optimal. The method of this routine activity is: Every morning wake up, the residents/clients are obliged to carry out morning prayers in congregation and prayer five times, holding recitals. For this reason, a Chancellor and Worship Practice program is required and other activities are closed at 10 pm. There is no time left, all the time utilized in the framework of resident recovery. The results of this Activity Program to Clients / Rehabilitated Patients are a healthy condition and can return to normal functioning in daily life. And do not return to using the Drug.